THE REPRODUCTION OF EDUCATIONAL INEQUALITY IN INDONESIA: AN EXAMINATION OF HINDERING FACTORS AND DIGITAL ACCESS IN RURAL AND URBAN SCHOOL SETTINGS - Faisal Rahman Dongoran; Reza Aditia (Sanata Dharma University Yogyakarta, 2026)
This study investigates factors contributing to educational disparities in Indonesia, particularly concerning school location and status. Employing a correlational research design, the study analyzed data from the 2022 Programme for International Student Assessment (PISA), focusing on the Indonesian school questionnaire dataset. The sample comprised 410 Indonesian schools, including 237 public and 173 private institutions. Pearson's chi-square test was utilized for statistical analysis to examine associations between categorical variables. Findings reveal significant relationships between school location and learning impediments related to teacher availability, physical infrastructure availability and quality, and digital resource availability. These issues are predominantly concentrated in public schools in rural areas, indicating a systematic disadvantage. While some challenges are also present in private schools, the impact is more pronounced in public institutions. The results suggest that educational inequality in Indonesia is structurally reproduced, perpetuating social and economic hierarchies. This necessitates comprehensive policy interventions that address both resource provision and underlying systemic issues.